ENVIRONMENTALLY SAFE TECHNOLOGIES IN THE CONSTRUCTION OF THE FOUNDATION - Pulatov Madaminjan (Journals Park Publishing, 2022)
This article focuses on environmentally friendly technologies in foundation construction, environmental aspects of chemical and physico-chemical reinforcement of grills.
Keywords: Marketing Strategy; Services Marketing; Ansoff Matrix